ITEMS ANALYSIS OF THE ACHIEVEMENT TESTS IN EFL CLASSROOMS - Nurbaeti, Adinda Putri; Taufiqulloh, Taufiqulloh; Sulistyawati, Anin Eka (LPPM Universitas Pancasakti Tegal, 2019)
This study focused on three kinds of item analysis towards the test items of the achievement tests. The validity and reliability were also provided as supporting functions. This study used quantitative data for the data source and some qualitative explanation to elaborate on the data. To gain the data analysis, the test papers and students answers sheets were collected from three achievement tests of SHS X, SHS Y, and SHS Z. Also, the first-grade students of those schools were as the sample of this study. The study revealed (1) the mean of item facility of three achievement tests categorized as medium test items (SHS X= 0,69; SHS Y= 0,55; and SHS Z= 0,44), while the mean of item discrimination of SHS X examined as good items (0,326) and the mean of item discrimination of SHS Y, SHS Z analyzed as satisfactory items (SHS Y= 0,245; and SHS Z= 0,244). Moreover, half of the distractor efficiency of those tests were accepted. Also, the validity and reliability of the achievement tests were found. Thus, it can be summarized that the achievement tests need to be improved since there are some items have high item facility and low item discrimination.